I am a Puppy - Rimson, Ole.; Illustrator,Olivia chin Muelller 2018 (New york Golden book press, 2018)
The classic board book I am a Puppy is back$1 (Bfully re illustrated and ready to be embraced by a new generation of children. Join Bruno, an adventurous puppy, as he plays with friends, leaps in the snow, takes a bath, and more! With simple words and adorable illustrations, this is perfect for toddlers.s
Keywords: English Story Book